Suitability Analysis of Community Development and Empowerment Programs in Mining Areas (Case of PT. GGB) - Aris Susilo; Denny Firmansyah; Rodiyah Nursani (Interdisciplinary Social Studies, 2026)
This study aims to evaluate the extent to which the Community Development and Empowerment Program (PPM) implemented by PT. Golden Great Borneo (GGB) in 2024 aligns with the actual needs of communities in the Ring 1 area, specifically Prabumenang and Banjarsari Villages, East Merapi District, Lahat Regency. Using a qualitative descriptive approach, the research combines analysis of official program documents and field observations with a structured Likert-scale survey involving 40 purposively selected beneficiaries. The study assesses eight core domains mandated in PPM guidelines: education, health, real income, economic independence, socio-religious-cultural aspects, environment, community institutions, and infrastructure. Findings show that the program received moderate appreciation from the community, with average perception scores ranging from 3.5 to 3.7. While education, health, and infrastructure were positively valued, key issues remain in benefit equity, long-term sustainability, and participatory implementation. The study contributes a novel, integrative assessment model combining community perception data with program alignment analysis. It concludes that future PPM efforts should adopt a more impact-oriented, community-driven approach, particularly by strengthening environmental programs, preventive health initiatives, post-training support, and local institutional capacity to ensure sustainable development in mining-affected regions.